The therapeutic landscapes concept as a mobilizing tool for liberation (Medicine Anthropology Theory, 2017)
In this reflection, I argue for using the therapeutic landscapes concept as a tool for mobilizing positive change in the world. I first lay out three major research areas in therapeutic landscapes inquiry, and provide a review of similarities in this area of inquiry in both health geography and medical anthropology. Next, I argue for the application of the therapeutic landscapes concept in liberating, if even in a small way, the growing population of the most vulnerable in our society, countries, and globe. I note two anthropological contributions that illustrate how the concept of therapeutic landscapes can be employed in liberating vulnerability, before discussing a work in progress, specific to an intentional ashram community with a mandate dedicated to world peace. I conclude by setting out the importance of this new direction for the future application of the therapeutic landscape concept as a tool for liberation.